Qur'anic Theology and the Mystical Shruks of Shaikh al-‘Ālam: A Comparative Analysis of Divine Unity and Moral Deviation - Sameeullah Bhat (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
Shaikh Nūr al-Dīn Nūrānī (Shaikh al-'Ālam) was one of the most influential spiritual figures in the history of Kashmir, where his Shruks contained profound theological, ethical, and mystical ideas. Although there is considerable research on his life and teachings, studies that systematically compare Shruks with Qur'anic theology—particularly regarding the concepts of tawḥīd, human moral deviance, spiritual responsibility, and tawbah—are still very limited. To fill the gap, this study employs an analytical-descriptive approach and thematic analysis to compare the Shruks of Shaikh al-'Ālam with relevant verses of the Qur'an. The study's results revealed a significant theological harmony between the Qur'anic message and the poetic expression of the Shaikh, particularly in terms of the oneness of God, prophetic guidance, primordial covenants, rejection of polytheism, and the transformative power of tawbah. Moreover, this research shows that the Shruks not only reflect the teachings of the Qur'an but also reinterpret them within the communicative and contextual framework of Kashmiri Sufism. The main contribution of this research lies in: (1) the presentation of a structured Qur'an–Sufi comparative model, (2) the strengthening of the understanding of Kashmiri Sufism as a theological expression firmly rooted in the Qur'an, and (3) the expansion of academic discourse on how local sufistic literature can function as a medium for the effective dissemination of Islamic theology across generations and cultures.